Try Not to Be Late! - the Importance of Delivery Service in Online Shopping - Coşar, Cihan; panyi, Krisztina; Varga, Akos (Organizations and Markets in Emerging Economies, 2017)
This study focuses on the role of delivery services in online purchases and their impact on customer satisfaction. Delivery service is one of the most important tasks of online purchase related to logistics, its performance directly influences the level of satisfaction. We aim to research what the online webshops and e-commerce businesses can or should do to have a positive impact on the customer satisfaction level. The research showed that delivery process in online purchases plays a significant role in customer satisfaction and in the decision making of whether or not one should purchase goods from a webshop. We contribute to the existing literature by widening it towards Eastern Europe and Turkey with our own conducted quantitative research. We released our questionnaire to an Eastern European and Turkish community as we were aiming to gather information on the emerging markets of Europe. We have utilized the following methods: frequency distribution, reliability testing, correlation analysis, linear regression analysis, normality test and one-way ANOVA to test our hypotheses. We found that delivery services and privacy policies play the most important part in ordering online in these communities, however, the income level of a person shows no significant relation towards customer satisfaction. We agree that any difficulties with the delivery process can have a negative effect on the purchase and the consumers, and that it influences how one can satisfy his or her needs.
Keywords: online marketing; consumer behavior; delivery services